The relationship between practicing recreational sports activities and psychological well-being and sports cultural awareness among female university students (Damu Journal of Sport Sciences, 2025)
The aim of the research was to identify differences in the practice of recreational activities among female university students (practicing and non-practicing recreational sports activities), differences in psychological well-being among female university students (practicing and non-practicing recreational sports activities), differences in cultural sports awareness among female university students (practicing and non-practicing recreational sports activities), differences in cultural sports awareness among female university students (practicing and non-practicing recreational sports activities), as well as identifying the relationship between practicing recreational activities and psychological well-being among female university students (practicing and non-practicing recreational sports activities), and understanding the relationship between practicing recreational activities and cultural sports awareness among female university students (practicing and non-practicing recreational sports activities). The research sample included a number of female university students (practicing and non-practicing recreational sports activities) for the academic year 2024-2025, totaling (200) students, with (100) practicing students. For recreational sports activities, (200) female students who did not participate in recreational sports activities were includedThe study reached the following conclusions:-1 There were statistically significant differences between the average responses of the research sample of female university students (practicers and non-practicers of recreational sports activities), in favor of those who practiced recreational sports activities, in terms of (recreational activity objectives, recreational activity content, and overall scale).-2 There were no statistically significant differences between those who practiced and non-practicers of recreational sports activities, in terms of (recreational activity capabilities and preferred recreational activities). -3There were statistically significant differences in psychological well-being between female university students (practicers and non-practicers of recreational sports activities), in favor of those who practiced recreational sports activities, in terms of (positive self-esteem, physical health, and overall scale). -4 There were no differences between female university students (practicers and non-practicers of recreational sports activities) in terms of (social relationships and psychological happiness).